Evaluating the impact of sustainable technology, resource utilization, and climate change on soil emissions: A CS-ARDL analysis of leading agricultural economies - Nazeer Ahmed; Guo Xinagyu; Mohamad Alnafissa; Mukut Sikder; Bonoua Faye (Cleaner Engineering and Technology)
Climate change has become a significant environmental issue humanity has faced in the last few decades. The primary cause of this is the greenhouse effect and carbon dioxide (CO2) emissions. The increase in agricultural emissions, deforestation, water stress, air, and soil pollution are results of the rise in global average temperature. Understanding how these gases move through the atmosphere is crucial for evaluating their roles in the greenhouse effect and, consequently, their influence on global warming and climate change. The main objective of this study is to estimate the role of water utilization, fertilizer input, surface temperature, economic growth, and environmental-related innovation technologies on greenhouse gas emissions. The study used an extensive panel data set covering the years 1990–2020 and employed advanced econometric techniques, namely CS-ARDL, PMG-ARDL, and Panel Causality of Dumitrescu and Hurlin framework. The study results show that climate change and water withdrawals have a positive and discernible effect on GHG emissions in the long and short run. The input of fertilizer and economic growth positively correlate with emissions derived from agriculture. It is also worth noting that sustainable technology illustrates a negative impact on GHG emissions, highlighting the importance of adopting sustainable technology to mitigate negative environmental impacts. This research also investigates the causality between farming climate change factors and GHG emissions, uncovering a unidirectional association between fertilizer input and climate change and a bidirectional causal relationship between water withdrawals, GDP, and sustainable technology. The results provide insightful information that researchers and policymakers may use to develop approaches connected to sustainability that address climate change, protect biodiversity, and guarantee sustainable agriculture.